The Concept of Modern Asceticism According to Max Weber Perspective(Case Study of Asceticism and Its Implications in The Theological Study Program Of UKSW) - Prayogo, Tonny Ilham; Syamsul Hadi Untung; Nurmala Indah; Nailatu Lutfiyah Sidqi; Shofia Ristiana Rahman; Nabila Hafitzah; Yesi Ameilia Pramesti; Aqila Thifal Khansa (Jurnal Studi Agama, 2025)
Asceticism, which is often identified as the act of mortification, is an attempt by a Christian to achieve Christlike perfection. In this act of asceticism, they are willing to abandon worldly pleasures and continue to strive for perfection. Asceticism is often associated with monastic practices to evoke behaviors or attitudes such as maintaining speech, restraining the soul, lack of food, seclusion, and limiting needs. The philosophy of contemporary asceticism is more dominant than the application of Max Weber's theory. The purpose of Asceticism was used by Weber as a potential transformation toward the "empowerment of monastic power". Lastly, Weber created Protestant asceticism and monastic revival. Weber drew asceticism from religious discussions of a realistic asceticism, derived from metaphysition. Max Weber's perspective on asceticism, is continuous with the education applied at Satya Wacana Christian University. This type of research is a literature review, the type of data collection is qualitative research, the research method is the study of Max Weber's thought figure, and the data analysis technique uses observation, interviews, and documentation. The result of this research is an indicator of one's success in religion depends on one's success in life in the world. This research uses a qualitative approach, with data processing focused on literature and observation.